Effects of beta-adrenergic antagonists (carvedilol and propranolol) on beta 2-adrenergic receptors and factor VIII levels in hyperthyroid cats - Janpen Bangsumruaj (Chulalongkorn University, 2008)
Thesis (M.Sc.)--Chulalongkorn University, 2006